Analisis Kemampuan Literasi Numerasi Pada Materi Matriks Ditinjau Dari Kemampuan Penyelesaian Masalah - Richo Hartanto; Farida Nursyahidah; Padmi Susilawati (Journal on Education, 2024)
Some students find it difficult to use matrix material analytically and critically. In addition, students also find it difficult to answer questions that require a high level of understanding. This study aims to analyze numeracy literacy skills in matrix material in terms of problem-solving abilities. This study is a qualitative study. The subjects of the study were 2 students of SMA N 11 Semarang City who had high and low category scores. Data collection was carried out through tests and interviews. The data analysis techniques used were reduction, presentation, and drawing conclusions. The credibility test in this study was carried out by utilizing triangulation techniques. The results of the study showed that students who had the highest test scores had very good numeracy literacy skills, while students who had the lowest test scores had less numeracy literacy skills